STUDY OF REACTION OF TRANS-[Pt(15NH3)2(H2O)2]2+ WITH N-ACETYL-L-CYSTEINE - Sutopo Hadi; Trevor G Appleton (Indonesian Journal of Chemistry, 2005)
A study of the reaction between trans-[Pt(15NH3)2(H2O)2](NO3)2 and N-acetyl-L-cysteine (H3accys) was undertaken to confirm the identity of the products formed. In alkaline solution, the platinum products observed were mononuclear species, while in acidic solution, the oligomeric products were obtained. The mass spectrometry of the reaction in alkaline solution showed a sulfur-bridged dinuclear platinum(II) species, trans-[{Pt(H2accys-S)2(15NH3)2}2((-H2accys-S)]+ giving m/z 948 and the lost of two ammines was observed.